Biomechanical and physiological comparison of barefoot and two shod conditions in experienced barefoot runners - Squadrone, R.; Gallozzi, C. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The first aim of this study was to assess how changes in the mechanical characteristics of the foot/shoe-ground interface affect spatio-temporal variables, ground pressure distribution, sagittal plane kinematics, and running economy in 8 experienced barefoot runners. The second aim was to assess if a special lightweight shoe (Vibram Fivefingers) was effective in mimic the experience of barefoot running. Methods. By using an instrumented treadmill, barefoot running, running with the Fivefingers, and running with standard running shoe were compared, analyzing a large numbers of consecutive steps. Foot/shoe-ground interface pressure distribution, lower limb kinematics, VO2 and heart rate data were simultaneously collected. Results. Compared to the standard shod condition when running barefoot the athletes landed in more plantarflexion at the ankle. This caused reduced impact forces and changes in stride kinematics. In particular, significantly shorter stride length and contact times and higher stride frequency were observed (P<0.05). Compared to standard shod condition, VO2 and peak impact forces were significantly lower with Fivefingers (P<0.05) and much closer to barefoot running. Lower limb kinematics with Fivefingers was similar to barefoot running with a foot position which was significantly more plantarflexed than in control shoe (P<0.05). Conclusion. The data of this study support the assumption that changes in the foot-ground interface led to changes in running pattern in a group of experienced barefoot runners. The Fivefingers model seems to be effective in imitating the barefoot conditions while providing a small amount of protection.